Vortex dynamics at the junction of Y-shaped microchannels in dilute polymer solutions - Park, Yong Min; Hong, Sun Ok; Lee, Pyung Cheon; Kim, Ju Min (Korea Australia Rheology Journal, 2019)
Understanding the vortex dynamics in polymer solutions is one of keys for the flow control in a wide range of polymer-related material processing applications. Vortex is generated due to the viscoelasticity of polymer solution, even if no vortex formation is expected under Newtonian flow conditions. In addition, the chaotic vortices generated in viscoelastic fluids have been recently exploited to mix different fluid streams in microfluidic devices. Herein, we investigated the vortex dynamics in dilute polyethylene oxide) solutions at the junction region of Y-shaped microchannels, which have been frequently used to mix two fluid streams. We report the formation of two types of vortices: A vortex at the stagnation point of the junction (center) and a lip vortex at the upstream of the sharp corner. Fluorescent microscopy revealed that the vortex dynamics was significantly affected by the angle between the two upstream channels, polymer concentration, and flow rate. We expect that this work will be useful for understanding the viscoelastic flow in microchannels and for the future design of microfluidic devices such as microfluidic mixers.
Keywords: microfluidic channel; polymer solution; viscoelastic fluid; vortex dynamics